Organizational structure of the german club Berliner TSC - Kalinowski, Paweł; Kulicka, Katarzyna; Pietranis, Dariusz; Nowakowska, Monika; Pietrzak, Michał; Wieczorek, Andrzej (Journal of Education, Health and Sport, 2019)
Football is one of the most popular sports disciplines in the world. Rules and regulations are well known but football clubs differ in terms of their level. There are many variables that can influence the success of football clubs. In this paper we made an attempt to describe how the football club from East Germany functions. Teams in a german club Berliner TSC served as our research material. The research was conducted in Berlin in 2017/2018 season. It was shown that recruiting strategies are similar in the german club and in polish clubs. What is different is their selection and goals of the clubs. It is considered that it is worth to adapt some of the solutions applied in german clubs to polish clubs.